Sturdevant's art and science of operative dentistry (Elsevier/Mosby, 2013)
Clinical significance of dental anatomy, histology, physiology, and occlusion; Dental caries : etiology, clinical characteristics, risk assessment, and management; Patient assessment, examination and diagnosis, and treatment planning; Fundamental concepts of enamel and dentin adhesion...